Porcine epidemic diarrhea virus strain FJzz1 infection induces type I/III IFNs production through RLRs and TLRs-mediated signaling - Chen, Pengfei; Zhu, Junrui; Yu, Jiarong; Liu, Ruilin; Lao, Mengqin; Yu, Lingxue; Gao, Fei; Jiang, Yifeng; Liu, Changlong; Tong, Wu; Liu, Huili; Tong, Guangzhi; et al. (Frontiers in Immunology, 2022)
Interferons (IFNs) including type Ⅰ/Ⅲ IFNs are the major components of the host innate immune response against porcine epidemic diarrhea virus (PEDV) infection, and several viral proteins have been identified to antagonize type Ⅰ/Ⅲ IFNs productions through diverse strategies. However, the modulation of PEDV infection upon the activation of the host’s innate immune response has not been fully characterized. In this study, we observed that various IFN-stimulated genes (ISGs) were upregulated significantly in a time- and dose-dependent manner in LLC-PK1 cells infected with the PEDV G2 strain FJzz1. The transcriptions of IRF9 and STAT1 were increased markedly in the late stage of FJzz1 infection and the promotion of the phosphorylation and nuclear translocation of STAT1, implicating the activation of the JAK-STAT signaling pathway during FJzz1 infection. In addition, abundant type Ⅰ/Ⅲ IFNs were produced after FJzz1 infection. However, type Ⅰ/Ⅲ IFNs and ISGs decreased greatly in FJzz1-infected LLC-PK1 cells following the silencing of the RIG-I-like receptors (RLRs), including RIG-I and MDA5, and the Toll-like receptors (TLRs) adaptors, MyD88 and TRIF. Altogether, FJzz1 infection induces the production of type-I/III IFNs in LLC-PK1 cells, in which RLRs and TLRs signaling pathways are involved, followed by the activation of the JAK-STAT signaling cascade, triggering the production of numerous ISGs to exert antiviral effects of innate immunity.